BLACKSPOT LOCATION AND RECOMMENDATION TO REDUCE NUMBER AND SEVERITY OF ACCIDENTS ON PURBALEUNYI TOLL ROAD - A. Caroline Sutandi; Wilson Gosalim (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
Toll roads, as land transportation infrastructure, have an important role in Indonesia. With a high number of road crashes in Indonesia, with about 40,000 people die on the road each year, the determination of blackspot locations is crucial. The aim of this study is to analyze blackspot location on a toll road in Indonesia and, furthermore, to provide recommendations in order to reduce number and severity of accident. A case study is carried out on a toll road, named Purbaleunyi Toll Road, in West Java. Accident rate value and UCL method are used in this study to determine blackspot locations. The results indicated that there are many blackspot locations along the toll road and recommended solutions provided are adherence to traffic regulation, adherence to vehicle worthiness,dissemination of road safety importance to road users, and the implementation of blackspot treatments continuously.Keywords: blackspot location, road crashes, toll road, blackspot treatments